Designing spray-based 3D printable cementitious materials with fly ash cenosphere and air entraining agent. (30th June 2019) - Lu, Bing; Qian, Ye; Li, Mingyang; Weng, Yiwei; Leong, Kah Fai; Tan, Ming Jen; Qian, Shunzhi
Highlights: An optimal mixture for spray-based 3D printing has been selected. Dimensional accuracy of spray-based 3D printing was improved. Effect of rheological properties on material distribution was discussed. Material design criteria for spray-based 3D printing were proposed. Abstract: 3D printing is a novel construction method, which utilizes sequential deposition of printable material to build structures. It contributes to the automation in civil engineering and offers advantages of design, greenness and efficiency. Similarities between conventional spray technology and 3D printing indicate the feasibility of spray-based 3D printing, which could enhance the automation in vertical and overhead construction. However, low dimensional accuracy of sprayed profiles with conventional materials greatly affects the quality of spray-based 3D printing. This study contributes to the development of cementitious material to improve the dimensional accuracy of spray-based 3D printing. In this study, fly ash cenosphere and air entraining agent were introduced to obtain the optimal mixture design considering the delivery and deposition requirements. Subsequent spray tests show that the optimal mixture has the smallest splash width and most uniform material distribution among all the designed mixtures. Analysis of deposition process reveals that the distribution of sprayed material is closely related with its rheological properties, which could guide the future research work on spray-based printing of cementitious materials.